The nematode serotonin-gated chloride channel MOD-1: A novel target for anthelmintic therapy - Rodriguez Araujo, Noelia (2022)
Anthelmintics are used to treat human and veterinary parasitic diseases and to reduce crop and livestock production loss associated with parasitosis. The free-living nematode Caenorhabditis elegans, a model system for anthelmintic drug discovery, has a serotonin (5-HT)-gated chloride channel, MOD-1, which belongs to the Cys-loop receptor family and modulates locomotory and behavioral functions. Since MOD-1 is unique to nematodes, it is emerging as an attractive anthelmintic drug target, but details of MOD-1 function are unclear. Here, we revealed novel aspects of MOD-1 function from the molecular level to the organism level and identified compounds targeting this receptor, which may provide new directions for anthelmintic drug discovery. We used whole-cell current recordings from heterologously expressed MOD-1 to show that tryptamine (Tryp), a weak partial agonist of vertebrate serotonin type 3 (5-HT3) receptors, efficaciously activates MOD-1. A screen for modulators revealed that GABAergic ligands piperazine (PZE) and muscimol reduce 5-HT-elicited currents, thus identifying novel MOD-1 allosteric inhibitors. Next, we performed locomotor activity assays, and we found 5-HT and Tryp rapidly decrease worm motility, which is reversible only at low 5-HT concentrations. Mutants lacking MOD-1 are partially resistant to both drugs, demonstrating its role in locomotion. Acting as an antagonist of MOD-1, we showed PZE reduces the locomotor effects of exogenous 5-HT. Therefore, Tryp- and PZE-derived compounds, acting at MOD-1 through different molecular mechanisms, emerge as promising anthelmintic agents. This study enhances our knowledge of the function and drug selectivity of Cys-loop receptors and postulates MOD-1 as a potential target for anthelmintic therapy.